Antimicrobial Activity and Characterization of Pomegranate Peel-Based Carbon Dots - Waseem Akhtar Qureshi (Hindawi Limited, 2021)
This investigation reports the use of agrowaste pomegranate peels as an economical source for the production of fluorescent carbon dots (C-dots) and their potential application as an antimicrobial agent. The carbon dots were prepared through low-temperature carbonization at 200°C for 120 min. The obtained C-dots were found to be small in size and exhibited blue luminescence at 350 nm. Further, the synthesized C-dots were characterized with the help of analytical instruments such as DLS, UV-visible, FT-IR, TEM, and fluorescence spectrophotometer. Antimicrobial activity of the C-dot PP was estimated by the agar diffusion method and MIC. S. aureus and K. pneumoniae are showing susceptibility towards C-dot PP when compared to the standard and showing a moderate activity against P. aeruginosa and resistance towards E. coli. The obtained C dot PPs were found to be around 5-9 nm in size confirmed from DLS analysis and supported by TEM. The synthesized C-dots were investigated to understand their microbial efficiency against pathogens and found to have antimicrobial efficiency. These results suggest that pomegranate peels are a potential source of carbon dots with antimicrobial efficiency.